2015
DOI: 10.1039/c5qi00176e
|View full text |Cite
|
Sign up to set email alerts
|

Water adsorption properties of a Sc(iii) porous coordination polymer for CO2 capture applications

Abstract: Water adsorption was investigated in the hydrostable Sc(iii) coordination polymer NOTT-400. This material performed CO2 capture under relative humidity (RH) conditions (20 and 10% RH). The maximum CO2 capture was obtained at 20% RH and 30 °C with a total amount of ∼10.2 wt%, representing a 2.5-fold increase in comparison with anhydrous conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 45 publications
2
44
0
Order By: Relevance
“…The positive effect of water inside the pores was confirmed also for MIL‐53(Al), NOTT‐400, Mg‐CUK‐1 and CAU‐10 …”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…The positive effect of water inside the pores was confirmed also for MIL‐53(Al), NOTT‐400, Mg‐CUK‐1 and CAU‐10 …”
Section: Introductionsupporting
confidence: 55%
“…[65] An even higher increase was achieved for the NOTT-401 MOF (Scandium-thiophene-2,5-dicarboxylic acid), reaching a 3.2-fold uptake increase under 5 % RH. [66] The positive effect of water inside the pores was confirmed also for MIL-53(Al) [67] , NOTT-400, [68] Mg-CUK-1 [69] and CAU-10. [70] For microporous MOFs only limited quantities of preadsorbed H 2 O can increase the carbon dioxide capture.…”
Section: Confinement Of Solvents Within Mofs Poresmentioning
confidence: 53%
“…[1] Particularly, the effect of water vapor addition has been studied in different materials, especially at low temperatures. [3,[11][12][13][14] Table 1 summarizes the total CO 2 capture capacities and cyclability conditions for different alkaline ceramics in the presence of water vapor as well as other materials in dry and wet conditions. [2,4, Among alkaline ceramics, Li 5 AlO 4 and Li 8 SiO 6 present high NOTT-401 30 9.9 wt% --Wet [37] Ni 3 (BTC) 2 40 2.5 --Dry [38] chemisorption capacities, which have been attributed to high Li/M (M ¼ Al or Si) atomic ratio.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Such behavior is also presented in the low-temperature range, where CO 2 capture capacity of some hydrotalcites is improved in the presence of water. [12,47,48] MOFs interaction with CO 2 is normally weak; hence, these materials begin to desorb CO 2 at T > 30 C. In some cases, it has been shown that small amounts of water increase CO 2 adsorption due to confinement effects induced by H 2 O, [14,37] but in the majority of these cases, water addition has a detrimental effect as these materials are saturated with water. [9,32] The CO 2 capture capacity of amines is increased in the presence of water, which is associated with the formation of bicarbonate and carbonate species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation